THE ROLE OF PLATELET-RICH FIBRIN FACILITATES THE HEALING OF GASTROCNEMIUS MUSCLE DEFECT: A PRELIMINARY STUDY ON ANIMAL MODEL - Dwikora Novembri Utomo; Kukuh Dwiputra Hernugrahanto (Journal Orthopaedi and Traumatology Surabaya)
Background: Scar formation has been a classical issue in the healing of skeletal muscle defect which will results in decrease of strength and function. Platelet-rich plasma (PRP) has been studied to enhance the healing of muscle defect. The disadvantages of it include the risk of immunologic reaction, time-consuming preparation, and lack of scaffold element. Platelet-rich fibrin (PRF) is a new generation of platelet concentrate that provides good source of growth factors and scaffold element necessary for the healing. This study is to provide a fondation of PRF preparation and implantation for the healing of experimental defect of gastrocnemius muscle in an animal model.